2013 IEEE Topical Conference on Biomedical Wireless Technologies, Networks, and Sensing Systems 2013
DOI: 10.1109/biowireless.2013.6613664
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the microwave permittivity of single particles

Abstract: We present a method to measure the permittivity of singles particles at microwave frequencies. Individual latex particles with diameters between 1 and 5 ȝm in de-ionized (DI) water are measured with a sensitive microwave sensor. An algorithm is developed to extract particle dielectric properties, which agree reasonably well with published results. The method is promising for single biological cell characterization at microwave frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…9 shows the S-parameters of microwave radiation system during the 107 microwave radiation cycles. The magnitudes of S11 and S21 were less than -16dB and -23dB, which confirmed that the microwave radiation system used in this study met the design requirements and showed good sensitivity [41]- [42]. S21 fluctuated with microwave exposure time and exhibited a declining trend of 3.8 dB overall.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…9 shows the S-parameters of microwave radiation system during the 107 microwave radiation cycles. The magnitudes of S11 and S21 were less than -16dB and -23dB, which confirmed that the microwave radiation system used in this study met the design requirements and showed good sensitivity [41]- [42]. S21 fluctuated with microwave exposure time and exhibited a declining trend of 3.8 dB overall.…”
Section: Resultssupporting
confidence: 67%
“…Dielectric properties of bones had obtained significant attentions to diagnose the osteoporosis due to the correlation between the dielectric property and bone mineral density [39] [40]. Further, dielectric coefficient measurement of single particle also induced plenty of interests on the differentiation of cancer cells [41] [42].…”
Section: Introductionmentioning
confidence: 99%
“…A method to measure the permittivity of single particles and yeast cells at microwave frequencies is presented in [8] and [9], respectively. An electrical approach for single-cell analysis, wherein a 1.6 GHz microwave interferometer detects the capacitance changes produced by single cells flowing past a coplanar interdigitated electrode pair, is demonstrated in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Power dividers, millimeter sized coplanar waveguides (CPW) and large (~200 μ L) polydimethylsiloxane (PDMS) wells are used therein. The technique shares the basic interference operating principle with the RF sensors [13], [14] and the microwave bridges [15], where only transmission scattering parameters are available. In this work, we show that interference-based sensors can be implemented with broadband quadrature hybrids.…”
Section: Introductionmentioning
confidence: 99%